2016
DOI: 10.1515/jbcpp-2016-0086
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and anti-inflammatory activities of isolated compounds of ethanol extract from Sanchezia speciosa Leonard’s leaves

Abstract: These compounds 1, 2, and 4 were isolated for the first time from the leaves of S. speciosa. These compounds showed strong antioxidant and anti-inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Over the past few decades, numerous plant‐derived natural products have been investigated for their activities against neurodegenerative in vitro hallmarks, including the reduction of oxidative stress, Aβ aggregation, and neuroinflammation . Among these compounds, flavonoids and related polyphenols are powerful antioxidants with potential therapeutic effects .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, numerous plant‐derived natural products have been investigated for their activities against neurodegenerative in vitro hallmarks, including the reduction of oxidative stress, Aβ aggregation, and neuroinflammation . Among these compounds, flavonoids and related polyphenols are powerful antioxidants with potential therapeutic effects .…”
Section: Introductionmentioning
confidence: 99%
“…gave a very positive result [6]. Similarly, the study of antioxidant effect by DPPH and antiinflammatory by the inhibition of albumine denaturation assay was reported by Thanh et al [7].…”
mentioning
confidence: 66%
“…Research has shown that an extract or compound capable of inhibiting protein denaturation is a potent anti-inflammatory agent (49,51). From the obtained results, the Phytexponent significantly inhibited heat-induced bovine serum albumin denaturation denoting its potential as an anti-inflammatory remedy (43,51).…”
Section: In Vitro Inhibition Of Protein Denaturation By the Phytexponentmentioning
confidence: 95%
“…Consequently, stabilization of the lysosomal membrane helps to either delay or decrease the release of proteases among other mediators, thereby decreasing inflammation (32,42). Since the human red blood cell (HRBC) membrane is analogous to that of the lysosome, a plant extract or compound that can inhibit hypotonicity-induced or heat-induced HRBC hemolysis can stabilize lysosomal membrane, thus averting its lysis leading to reduced inflammation (32,43). 1).…”
Section: In Vitro Anti-inflammatory Activity Of the Phytexponent Prepmentioning
confidence: 99%